Maternal vascular malformation in the placenta is an indicator for fetal growth restriction irrespective of neonatal birthweight. (November 2019) - Hendrix, M.L.E.; Bons, J.A.P.; Alers, N.O.; Severens-Rijvers, C.A.H.; Spaanderman, M.E.A.; Al-Nasiry, S.
Abstract: Introduction: To study the association between placental pathology and neonatal birthweight and outcomes, and whether a combination of first trimester biomarkers and fetal growth velocity can predict placental lesions. Methods: The presence of maternal vascular malperfusion (MVM) lesions (Amsterdam criteria) was recorded in a retrospective cohort of singleton pregnancies in the Maastricht University Medical Centre, 2011–2018. First trimester maternal characteristics and PAPP-A, PlGF and sFlt-1 levels were collected. Fetal growth velocities were calculated (mm/week) from 20 to 32 weeks for abdominal circumference, biparietal diameter, head circumference and femur length. Data were compared between neonates with 'small for gestational age' (SGA < p10) and different categories of 'appropriate for gestational age (AGA)': AGAp10-30, AGAp30-50 and AGA > p50 (reference), using one-way ANOVA and post hoc test. Results: There were significantly more MVM lesions in the SGA group (94.6% p < .0001), but also in the AGAp10-30 (67.3% p < .0001) and AGAp30-50 (41.6% p = 0.002), compared to the reference AGA group (19.3%). The prediction of MVM for a 20% false-positive rate, with maternal characteristics was25.2%. The addition of birthweight percentile gave a prediction of 51.7% for MVM. However adding placental biomarkers and fetal growth velocities (instead of birthweight percentile) to the maternal characteristics, gave a prediction of 81.8% (PPV 49.5%, NPV 53.7%). Discussion: Placental MVM lesions correlated inversely with birthweight even in AGA neonates, and was associated with slower fetal growth and more adverse outcome in SGA neonates. A combination of first trimester biomarkers and fetal growth velocity had good prediction of placental MVM lesions, as an indicator of fetal growth restriction irrespective of neonatal weight. Highlights: Appropriate for gestational age neonates show also maternal vascular malperfusion (MVM) lesions. The prediction of placental MVM lesions is higher using a combination of fetal growth velocities and placental biomarkers, than using birthweight percentiles. There is a subgroup of placental-mediated FGR fetuses in neonates born as AGA.